Customised retrofit of heat exchanger network combining area distribution and targeted investment - Lai, Yee Qing (Elsevier Ltd., 2019)
Heat exchanger network (HEN) retrofit plays a major role in solving environmental issues and improving plants’ performance. Development of HEN retrofit graphical tools has recently focused on detailed representation of existing HEN to facilitate retrofit problem-solving. This work presents a new customised approach for HEN retrofit that uses a combination of individual stream temperature versus enthalpy plot (STEP) to map hot and cold streams, a heat exchanger area versus enthalpy (A vs H) plot to minimise the required overall heat exchanger area and graphical cost screening tool and strategies to steer and customise a retrofit design toward a desired investment payback period. Application of the new retrofit methodology on a sunflower oil production plant shows comparable energy savings and 20% shorter payback period as compared other established retrofit methodologies.